Cost analysis of roll-to-roll fabricated ITO free single and tandem organic solar modules based on data from manufacture - Machui, Florian; Hosel, Markus; Li, Ning; Spyropoulos, Georgios; Ameri, Tayebeh; Sondergaard, Roar R.; Jorgensen, Mikkel; Scheel, Arnulf; Gaiser, Detlef; Kreul, Kilian; Lenssen, Daniel; Legros, Mathilde; et al. (Energy and Environmental Science, 2014)
We present a cost analysis based on state of the art printing and coating processes to fully encapsulated, flexible ITO- and vacuum-free polymer solar cell modules. Manufacturing data for both single junctions and tandem junctions are presented and analyzed. Within this calculation the most expensive layers and processing steps are identified. Based on large roll-to-roll coating experiments the exact material consumptions were determined. In addition to the data for the pilot scale experiment presented here, projections to medium and large scale scenarios serve as a guide to achieve cost targets of 5 €ct per W in a detailed material and cost analysis. These scenarios include the replacement of cost intensive layers, as well as process optimization steps. Furthermore, the cost structures for single and tandem devices are listed in detail and discussed. In an optimized model the material costs drop below 10 € per m which proves that OPV is a competitive alternative to established power generation technologies. This journal is © the Partner Organisations 2014.
Keywords: Engineering controlled terms: Coatings; Costs; Experiments; Manufacture; Optimization; Rolls (machine components); Solar cells Coating process; Optimized models; Pilot-scale experiments; Polymer Solar Cells; Power generation technology; Processing steps; Single junction; Tandem junction Engineering main heading: Cost accounting GEOBASE Subject Index: coating; cost-benefit analysis; numerical model; photovoltaic system; solar power